Preparation method and application of magnetic carbonized material for wastewater treatment
Magnetic carbonized materials are prepared by mixing biomass with sludge and pyrolyzed to impart magnetization, which solves the problems of low adsorption efficiency and difficulty in solid-liquid separation in antibiotic wastewater treatment, and achieves efficient pollutant removal and resource recycling.
Patent Information
- Application Number
- CN202411661982.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-10
AI Technical Summary
The adsorption efficiency of existing antibiotic wastewater treatment materials is low, the solid-liquid separation is difficult, and the sludge and biomass materials cannot be processed in time, resulting in secondary environmental pollution.
By mixing the biomass powder with dry sludge, pyrolytic carbonization and magnetic impartment, magnetic carbonized materials are prepared, and iron oxides are loaded by co-precipitation method to improve the magnetic properties and adsorption capacity of the materials, and effective adsorption and recovery of antibiotics are achieved.
It significantly improves the adsorption capacity of antibiotics, solves the problem of solid-liquid separation, realizes the recycling of materials, reduces production costs, and realizes the effective treatment of sludge and biomass resources.
Smart Images

Figure CN119281297A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sewage treatment, and in particular to a preparation method and application of a magnetic carbonized material for sewage treatment. Background Art
[0002] As a general antimicrobial drug, antibiotics have been widely used in the treatment of diseases in humans or animals and in livestock and poultry breeding. The abuse of antibiotics will lead to antibiotic residues. These residual antibiotics that exist in the environment for a long time will cause the production and spread of drug-resistant bacteria and resistance genes, causing varying degrees of damage to the human immune system and causing potential negative impacts on human life and health. At present, there have been frequent reports of antibiotics being detected in the effluent of sewage treatment plants, including common oxytetracycline, chlortetracycline, tetracycline, sulfonamide antibiotics, etc. Antibiotic pollution control is imminent.
[0003] Treatment methods for antibiotic wastewater involve conventional coagulation and sedimentation, membrane treatment, ultrasonic degradation, photocatalysis, adsorption, microbial electrochemical oxidation, etc. Among these technologies, adsorption has attracted widespread attention from scholars due to its unique advantages such as safety, non-toxicity, strong operation targeting, and rapid degradation. However, the existing adsorption materials have limited adsorption capacity and high prices, making them difficult to recycle. Therefore, developing a simple, novel, cheap and efficient material through regulation and modification has become a research hotspot for many experts and scholars.
[0004] With the acceleration of China's urbanization and industrialization, the output of municipal sludge has also increased year by year. The main methods of sludge treatment and disposal are landfill, incineration and composting, but these methods have obvious defects. Sludge landfill wastes a lot of land resources, and the leachate from the landfill is easy to pollute groundwater. Sludge incineration has problems such as high treatment costs and difficult treatment of residues after incineration. Sludge composting has the potential risk of pathogen spread and heavy metal pollution. In view of this, seeking a new sludge treatment method that is economically reasonable and compatible with environmental development is a hot topic in current sludge treatment research. Studies have shown that sludge-based carbon materials obtained by pyrolysis and carbonization of sludge have good adsorption effects, and heavy metals in sludge can be completely fixed during the pyrolysis and carbonization process to reduce secondary pollution. However, the sludge itself has problems such as small specific surface area and low adsorption capacity, which cannot meet the deep treatment of wastewater and meet the discharge standards.
[0005] Every year, a large amount of waste biomass that is not properly utilized and treated is not only a pollution to the local ecological environment, but also a waste of precious biomass resources. Hard shell peels (coconut, durian) are rich in cellulose. Therefore, using hard shell peels as biomass raw materials can not only realize the resource utilization of waste, but also solve the environmental pollution problem caused by itself, achieving the purpose of treating waste with waste.
[0006] The existing technology has problems such as low adsorption efficiency of antibiotic wastewater treatment materials, difficulty in solid-liquid separation and recycling, and secondary environmental pollution. Summary of the invention
[0007] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a preparation method and application of a magnetic carbonized material for wastewater treatment, and solve the technical problems in the prior art of low adsorption efficiency of antibiotic wastewater treatment materials, difficulty in solid-liquid separation, and inability to timely treat sludge and biomass materials.
[0008] In order to achieve the above technical objectives, the technical solution of the present invention provides a method for preparing a magnetic carbonized material for wastewater treatment, comprising the following steps:
[0009] S1, passing the biomass powder through a 100-mesh sieve and mixing it with the dried sludge, and then drying it to obtain a carbonized raw material;
[0010] S2, placing the carbonized raw material in a tubular furnace, heating it to 400-800° C. in a nitrogen atmosphere for a first pyrolysis carbonization, wherein the first pyrolysis carbonization is held for 1-3 h, and then cooling to obtain a carbonized material (BSC);
[0011] The material is magnetized by co-precipitation, and sodium hydroxide is used to adjust the iron oxidation into magnetic material under heating and stirring conditions and load it on the surface of BSC. The carbon content and iron oxide functional groups of the carbonized material itself are increased, and the material BSC has magnetic properties.
[0012] S3, preparing a mixture aqueous suspension of the waste residue from the inner bag of the heating pad and the carbonized material in a mass ratio of 1:1, adjusting the pH of the mixture aqueous suspension to 10-11, performing a co-precipitation magnetization reaction, and finally separating the precipitate by an external magnetic field;
[0013] S4. Put the precipitate into a muffle furnace, and perform a second pyrolysis carbonization at 400-500° C. in an air atmosphere. The holding time of the second pyrolysis carbonization is 1-2 h to obtain a magnetic carbonized material (BSMC).
[0014] Preferably, the biomass powder in S1 is one or more of coconut shell powder, peanut shell powder and durian shell powder.
[0015] Hard shell biomass contains a large amount of cellulose, hemicellulose and lignin, and has higher porosity and specific surface area after carbonization.
[0016] Preferably, the mass ratio of the biomass powder to the dry sludge in S1 is 1:0.5 to 1:2.
[0017] Adding biomass powder to the sludge in the sewage treatment plant can absorb the residual moisture in the sludge and make the raw materials more homogenous, thus reducing the energy consumption of drying.
[0018] Preferably, the organic matter content in the dried sludge in S1 is 50-60%.
[0019] Sludge with high organic matter content will produce a large amount of gas (such as water vapor, carbon dioxide, methane, etc.) during the high-temperature carbonization process, providing a rich multi-pore structure for the system.
[0020] Preferably, the temperature of the first pyrolysis carbonization in S2 is 500° C., and the insulation time of the first pyrolysis carbonization is 2 h.
[0021] Too low a temperature will result in incomplete carbonization and poor treatment effect. Too high a temperature will increase energy consumption and cause the pores formed by carbonization to collapse and become clogged, thus affecting the adsorption effect.
[0022] Preferably, the iron content in the waste residue of the inner bag of the heating pad in S3 is 50-70wt%.
[0023] Preferably, the solute concentration of the aqueous suspension of the mixture in S3 is 20 g / L.
[0024] By loading iron onto the carbonized material BSC, functional groups such as iron-oxygen bonds are added to the surface of the material, thereby improving its adsorption performance and making the material magnetic, enabling it to be recycled.
[0025] Preferably, the time of the co-precipitation magnetization reaction in S3 is 0.5-1.5 h, and the temperature of the co-precipitation magnetization reaction is 70-75°C.
[0026] An application of the magnetic carbonized material as described above comprises the following steps: adjusting the pH of antibiotic wastewater to 4-8, then adding the magnetic carbonized material to the antibiotic wastewater, adsorbing for 180-240 minutes at 25°C-35°C, and removing the magnetic carbonized material adsorbed with antibiotics from the system under the action of magnetic force. The antibiotic wastewater may be medical wastewater containing antibiotics, aquaculture wastewater, urban sewage, pharmaceutical factory wastewater, etc.
[0027] Preferably, the added amount of the magnetic carbonized material is 0.8-1.5 g / L, which can be understood as adding 0.8-1.5 g of magnetic carbonized material per liter of wastewater.
[0028] The present invention prepares a magnetic carbonized material by mixing biomass with dry sludge, and then subjecting the mixture to pyrolysis carbonization and co-precipitation magnetization. The material not only has good magnetic properties, which is convenient for separation and recovery in water treatment, but also has high porosity and specific surface area, providing more active sites for adsorption.
[0029] After carbonization and magnetization, the surface charge of the magnetic carbonized material is changed, and antibiotic molecules (such as tetracycline, penicillin, etc.) can be adsorbed on the surface of the material through electrostatic attraction.
[0030] Biomass forms a rich porous structure during pyrolysis, providing a larger specific surface area. This structure is conducive to the effective diffusion of antibiotic molecules and thus enhances adsorption capacity. Materials with high specific surface area can provide more active adsorption sites and increase the adsorption amount of antibiotic molecules.
[0031] The antibiotic molecules in the pores are firmly adsorbed on the surface of the material through physical effects such as van der Waals forces, hydrogen bonds, and π-π interactions. Chemical bonds are formed between the antibiotic molecules and the functional groups on the surface of the material, further improving the adsorption strength.
[0032] Sludge has a high carbon content, while fruit peels are rich in cellulose. Through magnetic modification, they have a high specific surface area and rich porous structure, which improves the adsorption capacity. In addition, carbonization and magnetization can also increase the number and types of functional groups on the surface of the material. The oxygen in the material can contribute its electrons to form a coordination complex, and antibiotics can also undergo complexation reactions through the metal oxygen bonds after magnetization. The π-π bonds on the benzene ring skeleton on the surface of the material form conjugates with antibiotic molecules. There are benzene rings and highly negative atoms in the antibiotic molecules. The active oxygen-containing functional groups (hydroxyl and carbonyl) of the material can participate in the adsorption process of antibiotics through strong π-π interactions and hydrogen bonds.
[0033] Traditional single sludge-based and biomass-based carbon materials have limited processing capacity due to their own specific surface area, pore size, and surface functional groups. Therefore, the present invention uses waste biomass as a recarburizer to coordinate with sludge to regulate the functional groups and physicochemical properties of carbon materials, thereby greatly improving the adsorption effect of the material. After the adsorption reaction of sludge-based and bio-based carbon materials prepared by traditional technology is completed, the adsorbent material can only be separated from the solution by natural sedimentation. There are problems such as difficulty in separating solids and liquids and generating secondary pollution, which makes it difficult to apply engineering. The present invention loads magnetic particles on sludge carbonized materials that have been regulated by bio-based materials, which solves the problem of solid-liquid separation while further improving the efficiency of carbon materials in removing pollutants from water, and realizes recycling by desorbing the carbon materials after adsorbing pollutants.
[0034] The present invention not only realizes the resource utilization of sludge waste, solves the environmental pollution problem caused by fruit peel waste and heating pad inner bag waste, but also treats antibiotic wastewater, achieving the purpose of treating waste with waste.
[0035] Compared with the prior art, the beneficial effects of the present invention include:
[0036] The invention has simple steps and easy conditions. Since waste sludge and hard-shell fruit peels are used as raw materials and waste materials of the inner bag of the heating pad are used as modified magnetic materials, the raw materials are widely available and the production cost is greatly reduced, thereby achieving pollution prevention and control and resource processing of solid waste.
[0037] (1) The present invention uses sludge and hard shell peel as raw materials, and after carbonization, iron is loaded on the material through the waste material of the inner bag of the heating patch, thereby improving the void structure and specific surface area of the magnetic carbonized material, enriching the functional groups on the surface of the material, thereby providing a large number of active adsorption sites, and significantly increasing the adsorption capacity of antibiotics. In addition, the material is loaded with magnetism to achieve recycling.
[0038] (2) Synergistic effect of physical and chemical adsorption mechanisms. Antibiotic molecules are adsorbed into the pores of the material by utilizing physical effects such as electrostatic attraction, van der Waals force, hydrogen bonding, and π-π interaction. At the same time, the antibiotic molecules react chemically with the functional groups on the surface of the material to form complexes, stabilizing the antibiotic molecules on the surface of the adsorption material, thereby improving the removal efficiency of the antibiotics.
[0039] (3) In the application of magnetic carbonized materials, the magnetic carbonized material in this application has an adsorption capacity of 113.95 mg / g for 100 mg / L antibiotic wastewater. The material has a treatment efficiency of 68% after five cycles of adsorption and desorption. This provides a new idea for renewable adsorption materials and data support for antibiotic wastewater treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] Figure 1 A hysteresis loop of a magnetic carbonized material prepared by a method for preparing a magnetic carbonized material for wastewater treatment provided in Example 1;
[0041] Figure 2 The Zeta potential diagram of a magnetic carbonized material prepared by a method for preparing a magnetic carbonized material for wastewater treatment provided in Example 1;
[0042] Figure 3 This is a diagram showing the magnetic separation effect of a magnetic carbonized material prepared by a method for preparing a magnetic carbonized material for wastewater treatment provided in Example 1. DETAILED DESCRIPTION
[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0044] Example 1
[0045] This embodiment provides a method for preparing a magnetic carbonized material for wastewater treatment, comprising the following steps:
[0046] S1. After passing the coconut shell powder through a 100-mesh sieve, the coconut shell powder is mixed with the dry sludge at a dry basis weight ratio of 1:0.5 and then dried to obtain a carbonized raw material, wherein the organic matter content in the dry sludge is 50%;
[0047] S2, placing the carbonized raw material in a tubular furnace, heating it to 500° C. in a nitrogen atmosphere for a first pyrolysis carbonization, wherein the first pyrolysis carbonization is held for 2 h, and then cooling to obtain a carbonized material;
[0048] S3, preparing a mixture suspension with a solute concentration of 20 g / L by mixing the waste residue of the inner bag of the heating pad with an iron content of 60 wt% and the carbonized material in a mass ratio of 1:1, adjusting the pH of the mixture suspension to 10 with 1 mol / L sodium hydroxide, stirring at 70° C. for 0.5 h to perform a co-precipitation magnetization reaction, and separating the precipitate by an external magnetic field;
[0049] S4. Put the precipitate into a muffle furnace, and perform a second pyrolysis carbonization at 500° C. in an air atmosphere. The second pyrolysis carbonization is performed for 2 hours to obtain a magnetic carbonized material.
[0050] The magnetic carbonized material prepared was subjected to magnetic analysis, and its hysteresis loop was as follows: Figure 1 As shown, it can be seen that the saturation magnetization Ms of the magnetic carbonized material (BSMC) prepared in this embodiment is 12.525emu / g, and the value of Mr / Ms is less than 25%, indicating that BSMC has superparamagnetic characteristics. When the external magnetic field disappears, the magnetization of BSMC can be rapidly reduced to 0. Therefore, BSMC can be well separated from the suspension after adsorbing antibiotics, and can be recycled conveniently and quickly.
[0051] Example 2
[0052] An application of the magnetic carbonized material described in Example 1 includes the following steps: adding the magnetic carbonized material to tetracycline wastewater with a concentration of 100 mg / L and pH=4, wherein the addition amount of the magnetic carbonized material is 0.8 g / L, adsorbing horizontally at 25°C for 180 minutes, removing the magnetic carbonized material adsorbed with antibiotics from the system under the action of magnetic force, determining the remaining tetracycline concentration using a spectrophotometer and calculating the adsorption efficiency.
[0053] Example 3
[0054] An application of the magnetic carbonized material prepared in Example 1 comprises the following steps: adjusting the pH of antibiotic wastewater to 6, then adding the magnetic carbonized material to tetracycline ion wastewater with a concentration of 100 mg / L, wherein the addition amount of the magnetic carbonized material is 0.8 g / L, adsorbing for 180 min at 25° C., removing the magnetic carbonized material adsorbed with antibiotics from the system under the action of magnetic force, measuring the remaining tetracycline concentration and calculating the adsorption efficiency.
[0055] Example 4
[0056] This embodiment is similar to embodiment 3, except that in this embodiment, the pH of the antibiotic wastewater is adjusted to 8.
[0057] Comparative Example 1
[0058] An application of the magnetic carbonized material prepared in Example 1. This comparative example is similar to Example 3, except that the pH of the antibiotic wastewater is adjusted to 3 in this comparative example.
[0059] Comparative Example 2
[0060] An application of the magnetic carbonized material prepared in Example 1. This comparative example is similar to Example 2, except that the pH of the antibiotic wastewater in this comparative example is adjusted to 9.
[0061] The results of Examples 2-4 and Comparative Examples 1-2 are shown in Table 1.
[0062] Table 1 Statistics of antibiotic adsorption effect at different pH
[0063] Group Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Adsorption rate / % 91.14 90.45 87.76 83.82 75.47
[0064] Zeta potential analysis was performed on the magnetic carbonized material prepared in Example 1. Figure 2 . It can be seen that the surface of the magnetic carbonized material is positively charged at pH < 3.9 and negatively charged at pH > 3.9. When pH = 4.0-8.0, tetracycline (TC) is in a zwitterionic form. Therefore, there is a strong electrostatic attraction between BSMC and TC, so the maximum adsorption amount of TC can be obtained when the pH of the adsorption solution is 4.0-8.0. If the pH value in the adsorption solution is not within this range, the charged properties of tetracycline and BSMC will change, resulting in mutual repulsion, which in turn affects the adsorption effect. This is consistent with the results of the above embodiments and comparative examples, indicating that electrostatic attraction is an important adsorption mechanism in the adsorption process.
[0065] After the material adsorbing antibiotics in Example 2 is separated by a magnet, the magnetic separation effect diagram is as follows: Figure 3, add 0.1M sodium hydroxide and ultrasonicate for 30 minutes, wash with pure water until neutral and dry, then add 0.8g / L to the antibiotic solution with a concentration of 100mg / L and pH=4, oscillate at constant temperature for 10 minutes at 25℃, measure the antibiotic concentration and calculate the adsorption efficiency, repeat 5 times. After 5 cycles of desorption and reuse for adsorption of antibiotics, the adsorption efficiency still reached 68%, a decrease of 23%.
[0066] When the adsorbent material containing antibiotics comes into contact with sodium hydroxide solution, the hydroxide ions may react chemically with the antibiotic molecules adsorbed on the surface of the adsorbent, resulting in changes or destruction of the structure of the antibiotic molecules, thereby desorbing them from the adsorbent surface. During the adsorption process, the antibiotic molecules bind to the functional groups on the surface of the adsorbent through electrostatic effects, hydrogen bonds or other forces. When sodium hydroxide solution is added, the hydroxide ions can replace the functional group ions bound to the antibiotic molecules through ion exchange, thereby destroying the binding force between the antibiotic molecules and the adsorbent, causing them to desorb from the adsorbent surface.
[0067] Example 5
[0068] This embodiment provides a method for preparing a magnetic carbonized material for wastewater treatment, comprising the following steps:
[0069] S1. Mix peanut shell powder through a 100-mesh sieve with dry sludge at a dry basis weight ratio of 1:1 and then dry to obtain a carbonized raw material, wherein the organic matter content in the dry sludge is 60%;
[0070] S2, placing the carbonized raw material in a tubular furnace, heating it to 400° C. in a nitrogen atmosphere for a first pyrolysis carbonization, wherein the first pyrolysis carbonization is held for 3 h, and then cooling to obtain a carbonized material;
[0071] S3, preparing a mixture suspension with a solute concentration of 20 g / L by mixing the waste residue of the inner bag of the heating pad with an iron content of 50 wt% and the carbonized material in a mass ratio of 1:1, adjusting the pH of the mixture suspension to 11 with 1 mol / L sodium hydroxide, stirring at 75° C. for 0.5 h to perform a co-precipitation magnetization reaction, and separating the precipitate by an external magnetic field;
[0072] S4. Put the precipitate into a muffle furnace, and perform a second pyrolysis carbonization at 500° C. in an air atmosphere. The heat preservation time of the second pyrolysis carbonization is 1 hour to obtain a magnetic carbonized material.
[0073] Example 6
[0074] An application of the magnetic carbonized material prepared in Example 5 comprises the following steps: adding the magnetic carbonized material to tetracycline ion wastewater with a concentration of 100 mg / L and a pH of 4, wherein the amount of the magnetic carbonized material added is 1.5 g / L, adsorbing for 180 min at 30° C., removing the magnetic carbonized material adsorbed with antibiotics from the system under the action of magnetic force, determining the remaining tetracycline concentration and calculating the adsorption efficiency.
[0075] Example 7
[0076] This embodiment is the same as Embodiment 6, except that the amount of magnetic carbonized material added in this embodiment is 0.9 g / L.
[0077] Example 8
[0078] This embodiment is the same as Embodiment 6, except that the amount of magnetic carbonized material added in this embodiment is 1.0 g / L.
[0079] Example 9
[0080] This embodiment is the same as Embodiment 6, except that the amount of magnetic carbonized material added in this embodiment is 1.2 g / L.
[0081] Comparative Example 3
[0082] This comparative example is the same as Example 6, except that the amount of magnetic carbonized material added in this example is 0.6 g / L.
[0083] The adsorption efficiency of tetracycline in Examples 6-9 and Comparative Example 3 is shown in Table 2.
[0084] Table 2 Statistical table of antibiotic adsorption effect at different addition amounts
[0085] Group Addition amount Adsorption rate / % Example 6 0.9 94.06 Example 7 1 95.53 Example 8 1.2 97.86 Example 9 1.5 98.96 Comparative Example 3 0.6 78.08
[0086] It can be seen that as the amount added increases, the adsorption efficiency increases significantly. When the amount added exceeds 0.9g / L, the increase in adsorption efficiency decreases and gradually stabilizes. This is mainly because as the amount added increases, more antibiotics are adsorbed to the surface of the material, and the adsorption rate is faster. When the amount added is greater than 0.8g / L, most of the antibiotics have been adsorbed, so the adsorption efficiency will not increase with the increase in the amount added.
[0087] Example 10
[0088] This embodiment provides a method for preparing a magnetic carbonized material for wastewater treatment, comprising the following steps:
[0089] S1. Durian shell powder and dry sludge are mixed in a mass ratio of 1:1 and then passed through a 100-mesh sieve to obtain a carbonized raw material, wherein the organic matter content in the dry sludge is 55%;
[0090] S2, placing the carbonized raw material in a tubular furnace, heating it to 600° C. in a nitrogen atmosphere for a first pyrolysis carbonization, wherein the first pyrolysis carbonization is held for 1 h, and then cooling to obtain a carbonized material;
[0091] S3, preparing a mixture suspension with a solute concentration of 10 g / L by mixing the waste residue of the inner bag of the heating pad with an iron content of 70 wt% and the carbonized material in a mass ratio of 1:1, adjusting the pH of the mixture suspension to 10.5 with 1 mol / L sodium hydroxide, stirring at 72° C. for 1 h to perform a co-precipitation magnetization reaction, and separating the precipitate by an external magnetic field;
[0092] S4. Put the precipitate into a muffle furnace, and perform a second pyrolysis carbonization at 450° C. in an air atmosphere. The second pyrolysis carbonization is performed for 1.5 h to obtain a magnetic carbonized material.
[0093] An application of the magnetic carbonized material prepared in this embodiment includes the following steps: adding the magnetic carbonized material to tetracycline ion wastewater with a concentration of 100 mg / L and a pH of 4, wherein the addition amount of the magnetic carbonized material is 0.8 g / L, adsorbing for 180 minutes at 35°C, removing the magnetic carbonized material adsorbed with antibiotics from the system under the action of magnetic force, measuring the remaining tetracycline concentration and calculating the adsorption efficiency.
[0094] Embodiment 11
[0095] An application of the magnetic carbonized material prepared in Example 8 comprises the following steps: adjusting the pH of antibiotic wastewater to 5, then adding the magnetic carbonized material to tetracycline ion wastewater with a concentration of 100 mg / L, wherein the addition amount of the magnetic carbonized material is 0.8 g / L, adsorbing at 35°C for 210 minutes, removing the magnetic carbonized material adsorbed with antibiotics from the system under the action of magnetic force, measuring the remaining tetracycline concentration and calculating the adsorption efficiency.
[0096] Comparative Example 4
[0097] This comparative example is similar to Example 8, except that the adsorption time in this comparative example is 150 min.
[0098] The adsorption efficiency of tetracycline in Examples 10-11 and Comparative Example 4 is shown in Table 3.
[0099] Table 3 Statistics of antibiotic adsorption effect
[0100] Group Adsorption time / min Adsorption rate / % Example 10 180 92.18 Embodiment 11 210 93.56 Comparative Example 4 150 84.46
[0101] As time goes by, the adsorption rate increases rapidly and finally tends to be flat. This shows that the process of magnetic carbonized material adsorbing antibiotics is: fast adsorption process, antibiotic molecules in the solution are adsorbed to the outer surface of the material; slow adsorption process, antibiotic molecules diffuse from the outer surface of the material to the internal pores and fill the pores of the material, or attach to the inner wall of the pores; after most of the antibiotics are adsorbed, the adsorption efficiency tends to be flat. It also shows that pore filling is an important mechanism in the adsorption process.
[0102] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a magnetic carbonized material for wastewater treatment, characterized in that: The following steps are involved: S1, passing the biomass powder through a 100-mesh sieve and mixing it with the dried sludge, and then drying it to obtain a carbonized raw material; S2, placing the carbonized raw material in a tubular furnace, heating it to 400-800° C. in a nitrogen atmosphere for a first pyrolysis carbonization, wherein the first pyrolysis carbonization has a holding time of 1-3 h, and then cooling to obtain a carbonized material; S3, preparing a mixture aqueous suspension of the waste residue from the inner bag of the heating pad and the carbonized material in a mass ratio of 1:1, adjusting the pH of the mixture aqueous suspension to 10-11, performing a co-precipitation magnetization reaction, and finally separating the precipitate by an external magnetic field; S4. Put the precipitate into a muffle furnace, and perform a second pyrolysis carbonization at 400-500° C. in an air atmosphere. The heat preservation time of the second pyrolysis carbonization is 1-2 hours to obtain a magnetic carbonized material.
2. The method for preparing a magnetic carbonized material for wastewater treatment according to claim 1, characterized in that: The biomass powder in S1 is one or more of coconut shell powder, peanut shell powder and durian shell powder.
3. The method for preparing a magnetic carbonized material for wastewater treatment according to claim 1, characterized in that: The mass ratio of the biomass powder to the dried sludge in S1 is 1:0.5 to 1:
2.
4. The method for preparing a magnetic carbonized material for wastewater treatment according to claim 1, characterized in that: The organic matter content in the dried sludge in S1 is 50-60%.
5. The method for preparing a magnetic carbonized material for wastewater treatment according to claim 1, characterized in that: The temperature of the first pyrolysis carbonization in S2 is 500° C., and the insulation time of the first pyrolysis carbonization is 2 h.
6. The method for preparing a magnetic carbonized material for wastewater treatment according to claim 1, characterized in that: The iron content in the waste residue of the inner bag of the heating pad described in S3 is 50-70wt%.
7. The method for preparing a magnetic carbonized material for wastewater treatment according to claim 1, characterized in that: The solute concentration of the aqueous suspension of the mixture in S3 is 20 g / L.
8. The method for preparing a magnetic carbonized material for wastewater treatment according to claim 1, characterized in that: The time of the co-precipitation magnetization reaction in S3 is 0.5-1.5 hours, and the temperature of the co-precipitation magnetization reaction is 70-75°C.
9. A use of the magnetic carbonized material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: adjusting the pH value of antibiotic wastewater to 4-8, then adding magnetic carbonized material into the antibiotic wastewater, adsorbing for 180-240 minutes at 25-35°C, and taking out the magnetic carbonized material adsorbed with antibiotics from the system under the action of magnetic force and recycling it.
10. The use according to claim 9, characterized in that: The added amount of the magnetic carbonized material is 0.8-1.5 g / L.